2020
DOI: 10.3390/molecules25173924
|View full text |Cite
|
Sign up to set email alerts
|

Automated Synthesis of Fluorine-18 Labeled CXCR4 Ligand via the Conjugation with Nicotinic Acid N-Hydroxysuccinimide Ester (6-[18F]SFPy)

Abstract: The C-X-C motif chemokine receptor 4 (CXCR4) is a seven-transmembrane G protein-coupled receptor that is overexpressed in numerous diseases, particularly in various cancers and is a powerful chemokine, attracting cells to the bone marrow niche. Therefore, CXCR4 is an attractive target for imaging and therapeutic purposes. The goal of this study is to develop an efficient, reproducible, and straightforward method to prepare a fluorine-18 labeled CXCR4 ligand. 6-[18F]Fluoronicotinic acid-2,3,5,6-tetrafluoropheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 49 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…A few research groups have reported analogues of SFB, with the aim for simplifying radiosynthesis protocols. Recently, a “fluorination on the Sep-Pak” method to prepare a prosthetic agent nicotinic acid N- hydroxysuccinimide ester (6-[ 18 F]SFPy) (Basuli et al, 2020 ) was published. The actual 18 F-fluorination takes place when passing the precursor compound through a solid-phase extraction cartridge pre-loaded with [ 18 F]fluoride.…”
Section: Design and Gallium-68 Labelling Of Ph-triggered Aggregation mentioning
confidence: 99%
“…A few research groups have reported analogues of SFB, with the aim for simplifying radiosynthesis protocols. Recently, a “fluorination on the Sep-Pak” method to prepare a prosthetic agent nicotinic acid N- hydroxysuccinimide ester (6-[ 18 F]SFPy) (Basuli et al, 2020 ) was published. The actual 18 F-fluorination takes place when passing the precursor compound through a solid-phase extraction cartridge pre-loaded with [ 18 F]fluoride.…”
Section: Design and Gallium-68 Labelling Of Ph-triggered Aggregation mentioning
confidence: 99%
“… 92 Despite moderate results of 68 Ga-NOTA-NFB, other modifications to the T140 derivatives are under development. 16 , 93 …”
Section: New Reports Of Radiolabeled Amino Acid Based Molecules Usedmentioning
confidence: 99%
“…Unfortunately, the clearance pattern of 68 Ga-NOTA-NFB exhibited very high splenic and liver uptake, which challenged the application of 68 Ga-NOTA-NFB PET/CT in high contrast clinical imaging of CXCR4 expression . Despite moderate results of 68 Ga-NOTA-NFB, other modifications to the T140 derivatives are under development. , …”
Section: New Reports Of Radiolabeled Amino Acid Based Molecules Used ...mentioning
confidence: 99%
See 2 more Smart Citations